A new model for rolling element bearing defect size estimation. (January 2018) - Chen, Aoyu; Kurfess, Thomas R.
Highlights: Entry signal is used to find the moment when the ball center arrives entry edge. All the parameters for the estimation can be obtained from the vibration signal. Experiments were performed on a CNC machine tool rather than test rigs. Abstract: A new model based on the Hertzian contact theorem is proposed to estimate the size of a line spall defect located on the bearing's outer race. The entry point can be determined from the ball-race geometry relation, while the exit point can be identified from the time domain signal. Therefore, the defect size can be estimated from the vibration signal without requiring additional bearing load and stiffness measurements. Experiments were performed on a 3-axis CNC machine tool at speeds ranging from 500 to 3000 rpm and three line spall defects were estimated using the proposed method. The proposed model is demonstrated to estimate defect size with minimal speed related error, offset error, and standard deviation.